A behavioural game theory perspective on the collaboration between innovative and entrepreneurial firms. (2017) - Chou, P. Ben; Bandera, Cesar; Thomas, Ellen
From a behavioural game theory perspective, we characterise the strategic interactions between a smaller innovative firm and a larger entrepreneurial firm as they try to form a strategic alliance to commercialise a technological invention. If the innovative firm is not too overconfident and the entrepreneurial firm is not too complacent, it is likely that the game is similar to the stag hunt game with two Nash equilibria. However, in addition to securing the funds needed to commercialise the invention, both firms need to contribute sufficient and complementary efforts when they choose to cooperate. The larger entrepreneurial firm can also expedite the commercialisation process if it chooses the cooperative strategy first and takes the initiative to offer financial and entrepreneurial assistance to the smaller innovative firm.